PENGARUH PROFITABILITAS, LIKUIDITAS, KEPEMILIKAN PUBLIK DAN REPUTASI KAP TERHADAP KETEPATAN WAKTU PELAPORAN - Umi Murtini; Yusefin Puspa Tirtaningrum (Jurnal Riset Akuntansi dan Keuangan, 2013)
Punctuality is important character in reporting the financial report besides main report and note of financial report. Delay of financial report publication will destract its user. Demand of its punctuality in delivering financial report of public enterprise in Indonesia is regulated on UU No. 8, 1995 on capital market and based on BAPEPAM chief’s decision No.36/PM/2003 on regular financial report obligation. This research aims to test the impact of profitability, liquidity, public ownership and KAP reputation towards punctuality on reporting the financial report. The test is using logistic regression analysis. The result shows that profitability, liquidity, and KAP reputation do not affect toward the punctuality on reporting the financial report, meanwhile the public ownership affects the punctuality on reporting the financial report. Keywords: punctuality, KAP reputation, financial report.